Diversity of Edible Fruit Species in Gunung Leuser National Park Area, Aceh Tamiang - Albian Mubarak; Enni Suwarsi Rahayu; Amin Retnoningsih (Jurnal Penelitian Pendidikan IPA, 2023)
Aceh Tamiang Regency, located in the northern part of Sumatra Island with an area of 1.957.02 kmÂ², is part of the Leuser Ecosystem, famously known as the Gunung Leuser National Park-TNGL. The remarkable biodiversity in TNGL has earned it recognition as a national park and wildlife sanctuary. Threats to this biodiversity include illegal logging, land conversion, hunting, and wildlife trafficking. This study aimed to identify the diversity of edible fruit species in the Aceh Tamiang region of TNGL as an initial step in conservation and utilization efforts for fruit biodiversity. The genetic resources of edible fruit plants in this area hold significant potential for enhancing the quality and quantity of fruits in Indonesia. Hence, conservation and sustainable management are crucial for fruit plant development. The research was conducted in Bandar Pusaka, Tamiang Hulu, and Tenggulun. The exploration discovered 81 species of edible fruits from 27 families. Tenggulun had the highest number of species (61 species), followed by Bandar Pusaka (53 species) and Tamiang Hulu (44 species). Species like Mangifera odorata Griff., Garcinia mangostana L., Pometia pinnata J.R. Forst. & G. Forst., and others were found in all locations. The highest diversity index was in Tenggulun (HI 3.31), followed by Bandar Pusaka (2.88), and the lowest in Tamiang Hulu (2.39). Species evenness ranged from 0.63 to 0.81, indicating moderate and stable evenness levels. Species dominance was low, with values ranging from 0.007-0.009.Â